2017
DOI: 10.1002/nop2.100
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study on individual experiences of chronic hepatitis B patients

Abstract: AimThe aim of this study was to explain the perception of patients with chronic hepatitis B regarding problems in the Iranian society.DesignDescriptive qualitative research.MethodsIn this qualitative study, 27 patients with chronic hepatitis B in Iran were selected through purposive sampling. The data were collected over 22 months, in 2015–2016, by means of semi‐structured interviews and field notes. The interview transcripts were coded using MAXQDA10 software®. To extract categories and themes, the thematic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
1
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 34 publications
0
31
1
2
Order By: Relevance
“…Some studies have indicated that patients refused screenings and follow-up because of the fear of unfavourable results and social stigma (Ezbarami et al, 2017;Yang, 2013), but the current study did not produce similar results. Instead, results emphasised that work- Furthermore, if patients perceive that the health care provided is not helpful to them, they are more likely to neglect opportunities to link with the self-management programme of hepatitis B.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Some studies have indicated that patients refused screenings and follow-up because of the fear of unfavourable results and social stigma (Ezbarami et al, 2017;Yang, 2013), but the current study did not produce similar results. Instead, results emphasised that work- Furthermore, if patients perceive that the health care provided is not helpful to them, they are more likely to neglect opportunities to link with the self-management programme of hepatitis B.…”
Section: Discussioncontrasting
confidence: 82%
“…Chronic hepatitis B may develop into severe liver disease. Patients may refuse screenings and follow-ups because they fear unfavourable results and negative judgement from other people (Ezbarami, Hassani, Tafreshi, & Majd, 2017;Yang, 2013). In the disease self-management process, individual awareness, managerial skills and executive abilities are required to solve the physiological, psychological and social problems caused by chronic hepatitis B (Kong et al, 2018;Yang, 2013).…”
mentioning
confidence: 99%
“…All except two of these 40 , 41 clearly described data collection procedure and the research context. Analysis of data may be less robust in four studies 41 , 42 , 55 , 56 since there was no description of how many researchers analysed the results and how differences in extracted themes and codes were resolved between researchers. Two studies did not provide details of ethics approval 40 , 42 ; three studies did not provide a rationale for using the selected study methodology 40 , 43 , 60 ; seven studies did not report in detail on their study limitations 29 , 42 , 43 , 53 , 55 , 56 , 60 .…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, in other illness experience studies, alcohol reduction and fatty food avoidance were regarded as a burden by patients with CHB. 50 67 Taking drinking as an example, drinking is a normal part of work life and served to improve social relationships in many cultures. 68 A study showed that drinking with colleagues after work has a positive impact on fostering harmony among colleagues and on deciding who will be in charge of group collaborations.…”
Section: Discussionmentioning
confidence: 99%
“…As other studies have shown, positive framing and a spirit of dedication are essential for having healthier behaviour and a better mood. 50 78 Nevertheless, few studies have addressed the effects of specific competencies, including effective problem-solving skills and social skills. In our study, individuals with high problem-solving skills and social skills can buffer behaviour-based conflicts.…”
Section: Discussionmentioning
confidence: 99%